2014
DOI: 10.2106/jbjs.l.01690
|View full text |Cite
|
Sign up to set email alerts
|

Initial Instability in Total Ankle Replacement: A Cadaveric Biomechanical Investigation of the STAR and Agility Prostheses

Abstract: Stable initial implant fixation will likely improve clinical outcomes of total ankle replacement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 43 publications
0
18
0
1
Order By: Relevance
“…High levels of micromotion of cementless orthopaedic prostheses (>50–150 µm; [8], [9], [10]) are thought to impede osseointegration at the bone-implant interface, thereby hampering fixation [11] and potentially leading to clinical loosening [8], [9], [12]. Accordingly, micromotion of two TAR prosthesis designs has been assessed experimentally to evaluate the implant primary stability using optical tracking [13].…”
Section: Introductionmentioning
confidence: 99%
“…High levels of micromotion of cementless orthopaedic prostheses (>50–150 µm; [8], [9], [10]) are thought to impede osseointegration at the bone-implant interface, thereby hampering fixation [11] and potentially leading to clinical loosening [8], [9], [12]. Accordingly, micromotion of two TAR prosthesis designs has been assessed experimentally to evaluate the implant primary stability using optical tracking [13].…”
Section: Introductionmentioning
confidence: 99%
“…The tibial component of the STAR was most susceptible to normal motion on the bone surface, especially in plantar flexion-dorsiflexion and inversion-eversion loading. On average, of the three loading directions, the internalexternal rotation resulted in the smallest relative motions of both of the STAR components since the device allowed for unconstrained rotation about this axis [19].…”
Section: Star Ankle Prosthesismentioning
confidence: 99%
“…The motion magnitudes were quite large, with values exceeding 1, 000 mm for the Agility talar component in plantar flexiondorsiflexion and in inversion-eversion. Large motions at the bone-implant interface, resulting from weak initial fixation, may inhibit implant osseointegration early in the healing process, and it may also contribute to the overall likelihood of implant failure resulting from aseptic loosening [19].…”
Section: Outcomes Of Tarmentioning
confidence: 99%
See 1 more Smart Citation
“…Spirt et al reported that most TAR loosening failures observed clinically were related to the talar components. This could possibly due to the inability to achieve primary stability of the prosthesis fixation at the bone‐prosthesis interface between the talar component and talus bone . Moreover, the primary stability has been extremely crucial since most of the major commercial TARs are moving towards cementless design and are completely dependent on the bone ingrowth for fixation .…”
Section: Introductionmentioning
confidence: 99%